Explaining South Africa's quiet diplomacy towards Zimbabwe since 2000: the dilemma of a pluralist middle power - Gcoyi, Thembinkosi (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2006)
This study is a contribution to the literature on South Africa's foreign policy since 2000-2004. It provides a theoretical framework within which South Africa's foreign policy should be understood. It attempts to explain the contradictions that have been apparent in South Africa's foreign policy by looking at the constraints inherent in South Africa's position as an emerging middle power. It argues that South Africa's pluralist inclinations are constrained by Africa's evolving multilateral forums and that South Africa's preference for such undermines the realization and achievement of her foreign policy principles and goals. It also argues that as a realist middle power, South Africa is constrained the ambivalence shown by the region towards her exercising leadership in the region. This is due to South Africa's history of destruction in Southern Africa in the 1980's. South Africa's quiet diplomacy towards Zimbabwe provides the focal point for the study. The study argues that it is not the case that South Africa is not concerned with human rights abuses in Zimbabwe. Instead, this concern has been expressed in ways that do not tarnish South Africa's own image in Africa. This has been done by engaging Zimbabweans through multilateral forums. This study concludes that this strategy failed to bring about resolution to the Zimbabwean crisis.
Keywords: Middle powers|Conflict management|Zimbabwe -- Foreign relations -- South Africa|South Africa -- Foreign relations -- Zimbabwe|South Africa -- Politics and government -- 1994-|Zimbabwe -- Politics and government -- 1980-